من ناحية المادة الدراسيةـ MTsS Darul Ulum Banda Aceh تدريس النحو بـــــ - Salsabila, Cut Nadia; Mahmud, Salami; Fajriah, Fajriah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
Based on the results of the researcher’s observation on the first grade students at MTsS Darul Ulum Banda Aceh, Not all of the students understand the material mubtada’ khabar well. This is because the teacher only uses one book teaching. Therefore, researcher are interested in developing Arabic teaching material mubtada' khabar. The purposes of this study were to determine the steps in developing teaching material, to determine students’ responses to teaching the developed material. And to determine the achievement of the teaching materials. The researcher used the Research and Development method, using the ADDIE model. The instrument used an expert validation sheet and student response questionnaire. The samples of this research are 20 male students from Class VII/I. The results of this research are: 1) The steps in the development of teaching materials consist of analysis, design, development, implementation, and evaluation. 2)Teaching materials can be used after an assessment by experts, the results from material experts are 75% in the category (worthy), the results from design experts are 95% in the category (very worthy), the results from Arabic teacher experts are 85% in the category (very worthy). 3) The results of students’ responses to the teaching materials developed on mubtada’ khabar were positive in grade 94,5% (stronly agree).